Adsorption Study of Methylene Blue onto Power Activated Carbon Prepared from Ananas Comosus Peels - Nasiru Yahaya; Ibrahim Ali; Kolo Modu; Shehu Adamu (Nanochemistry Research, 2023)
The adsorption capacity of activated carbon powder prepared from Ananas comosus peels for the removal of methylene blue dye as a contaminant was investigated. These adsorbents were prepared by carbonization at 500 oC with activating agents (K2CO3, H3PO4 and NaOH) and characterized using Fourier Transform Infrared. Plackett-Burman Design was used to analyze the various factors affecting adsorption. Response surface methodology techniques was employed to determine the optimal condition of pH=12.6569 and adsorbent dosage of 1.1864. At the optimal condition, the activated carbon yielded the highest removal of methylene blue (99.4 %). The experimental data best fitted the pseudo-second order kinetic model, except for acid activation (ACP-A) which agreed with inter-particle diffusion model with the determination coefficient of 0.9939. The adsorption isotherms for all the prepared carbons were highly consistent with Langmuir adsorption isotherm. This study demonstrates that the activated carbon prepared from Ananas comosus peels can be efficient in removing methylene blue dye contaminants from aqueous solution.